2021
DOI: 10.1111/coa.13847
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of endolymphatic hydrops and its correlation with Meniere’s disease clinical features

Abstract: Objective:We aimed to quantitatively evaluate the degree of endolymphatic hydrops and its correlation with the clinical features of Meniere's disease. Methods:We retrospectively collected data from patients with Meniere's disease who underwent gadolinium-enhanced magnetic resonance imaging (MRI) at our department from January 2018 to December 2019. Mimics software was used to perform three-dimensional modelling of the labyrinth, and volume information was obtained to calculate the endolymphatic hydrops index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(21 reference statements)
0
8
3
Order By: Relevance
“…However, degree of cochlear EH decreased with MD stage when it changed from stage 3 to 4, as did degree of cochlear and vestibular EH at the second hospitalization. However, our results were not entirely consistent with a previous study ( 39 ). This may have been because Sun et al ( 39 ) analyzed the relationship between total EH index and MD stage and did not separately analyze the relationship of cochlear EH index or vestibular EH index with MD stage.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, degree of cochlear EH decreased with MD stage when it changed from stage 3 to 4, as did degree of cochlear and vestibular EH at the second hospitalization. However, our results were not entirely consistent with a previous study ( 39 ). This may have been because Sun et al ( 39 ) analyzed the relationship between total EH index and MD stage and did not separately analyze the relationship of cochlear EH index or vestibular EH index with MD stage.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results were not entirely consistent with a previous study ( 39 ). This may have been because Sun et al ( 39 ) analyzed the relationship between total EH index and MD stage and did not separately analyze the relationship of cochlear EH index or vestibular EH index with MD stage. Alternatively, Sun et al only analyzed once examination showing the relationship between EH and MD stage, which was consistent with our vestibular EH at the first hospitalization.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At present, endolymphatic hydrops can be visualized by injecting gadolinium contrast agent, which increases the diagnostic rate of Meniere's disease ( 33 ). Scholars have confirmed that the degree of endolymphatic hydrops is related to the stage of Meniere's disease, low-frequency hearing threshold, EchoG, and VEMP asymmetry ratio ( 34 , 35 ). Meniere's disease is mostly attributed to endolymphatic hydrops in the inner ear.…”
Section: Discussionmentioning
confidence: 94%
“…Meniere's disease is a clinical syndrome characterized by recurrent episodes of spontaneous vertigo, unilateral fluctuating sensorineural hearing loss, tinnitus, and sufficient hearing 1,2 . Endolymphatic hydrops is considered as the pathophysiological basis of the disease, which has been confirmed in anatomical pathology studies and recent magnetic resonance imaging (MRI) 3,4 .…”
Section: Resultsmentioning
confidence: 99%